Adsorption of the lamellar phase of aerosol-OT at the solid/liquid and air/liquid interfaces - Li, Z; Weller, A; Thomas, R; Rennie, A; Webster, J; Penfold, J; Heenan, R; Cubitt, R (1999)
The adsorption of concentrated solutions of di-2-ethylhexylsodium sulfosuccinate (Aerosol-OT or AOT) at hydrophilic solid/aqueous and air/aqueous solution interfaces was followed by neutron specular reflection. Reflectivity profiles were recorded of protonated AOT in D2O at concentrations of 2 and 5 wt % and over a range of temperatures. Sharp diffraction peaks characteristic of a lamellar phase were observed, and the repeat spacing of the peaks was very sensitive to temperature. The bulk phase diagram in this concentration range over the temperature range 0-65°C was also studied using neutron small angle scattering. For the bulk solution containing 5 wt % AOT, the lamellar phase at 5°C had a repeat distance of 370 ± 30 Å, which dropped to about half that value at 35°C, and to only 115 Å at 65°C. The lamellar spacing decreased as the AOT concentration was lowered; for example, from 325 Å at 5 wt % to 225 Å at 1 wt %, at 15°C. Over some of the concentration and temperature range narrow diffraction peaks were observed for the lamellar phase adsorbed at both interfaces, indicating long-range order in the direction normal to the surface. The repeat spacing in the adsorbed lamellar phase was generally 10-20% smaller than in the bulk solution. Although addition of small amounts of electrolyte (0.1 and 1 mM NaBr) had only a small effect on the small angle scattering from the bulk lamellar phase, it caused the disappearance of the adsorbed lamellar phase. These observations are consistent with an overall attraction of the lamellar phase to the surface in the absence of added electrolyte.